Tetracyclines in COVID‐19 patients quarantined at home: Literature evidence supporting real‐world data from a multicenter observational study targeting inflammatory and infectious dermatoses. Issue 1 (29th December 2020) - Gironi, Laura Cristina; Damiani, Giovanni; Zavattaro, Elisa; Pacifico, Alessia; Santus, Pierachille; Pigatto, Paolo Daniele Maria; Cremona, Ottavio; Savoia, Paola
Abstract: Tetracyclines (TetraC) are widely used in dermatology for both inflammatory and infectious dermatoses; recently both in vivo and in vitro studies started to suggest also a potential antiviral effect. During COVID‐19 outbreak, several dermatological patients contracted SARS‐CoV‐2 experiencing only mild symptoms, but no protocol were approved. A multicenter prospective observational study that enrolled COVID‐19 patients visited with teledermatology and undergoing TetraC was performed. About 38 adult outpatients (M/F: 20/18, age 42.6 years [21‐67]) were enrolled. During the TetraC treatment, symptoms resolved in all patients within 10 days. Remarkably, ageusia and anosmia disappeared in the first week of TetraC treatment. TetraC seem a promising drug to treat COVID‐19 outpatients with mild symptoms.